Atom probe tomography and numerical study of austenite stabilization in a low carbon low alloy steel processed by two-step intercritical heat treatment. (August 2017) - Xie, Z.J.; Shang, C.J.; Subramanian, S.V.; Ma, X.P.; Misra, R.D.K.
Abstract: Film-like retained austenite with a volume fraction of 10% was obtained in a Fe-0.08C-0.5Si-2.4Mn-0.5Ni (wt%) steel via a two-step intercritical treatment. The retained austenite exhibited ultra-high stability even on cooling to −100 °C. Atom probe tomography indicated notable enrichment of C (0.43 wt%) and Mn (6.6 wt%) in retained austenite. The ultra-high stability of austenite in low carbon low alloy steel is attributed to the combination of partitioning of C and Mn to austenite and the size effect of ultrafine austenite based on thermodynamic analysis. It is underscored that controlled growth of reverted austenite is important for austenite stabilization. Graphical abstract: